Do women prefer face-to-face treatment for insomnia?: Gender-specific aspects of the utilization of online counselling for sleep disorders Bevorzugen Frauen Face-to-Face-Beratung bei Insomnie?: Genderspezifische Aspekte bei der Inanspruchnahme von Onlineberatung bei Schlafstörungen - Retzer, Lukas; Reindl, Richard; Zauter, Sigrid; Richter, Kneginja (Somnologie, 2021)
Background: Shift work is associated with high rates of sleep disorders. Digital cognitive behavioral therapy for insomnia (dCBT-I) might be an appropriate tool to treat this target population. Dropout rates in dCBT‑I trials are relatively high. The literature suggests that women prefer face-to-face contact in psychotherapy settings. Objectives: We implemented an online platform to provide dCBT‑I specifically for shift workers. In this secondary analysis, we aimed to examine gender differences between dropouts and completers in our trial. We hypothesized that a higher percentage of women would drop out of the study compared to men. Materials and methods: We perform post-hoc analysis (chi-square tests and t‑tests) on the data from our four-week dCBT‑I trial. Specifically, we compared dropout rates and time of dropout by gender. Results: The trial was initiated by N = 50 participants (13 female/37 male), of which 56% did not complete the program. Dropout rates are significantly higher in women (77%) than men (49%; p = 0.034). There are no significant gender differences regarding time of dropout or other sample characteristics, such as total sleep time, symptom severity, or age. Conclusions: Even though they suffer from just as many symptoms of insomnia, female shift workers may be more likely to drop out of dCBT‑I programs than their male counterparts. This highlights the need for additional research to improve engagement and adherence in dCBT‑I, specifically for women. The relatively small sample size limits the transferability of these results.
Created from Fastlane, Scopus look-up
Keywords: Cognitive behavioral therapy; Psychotherapy; Shift work schedule; Telemedicine; Women’s health